2022
DOI: 10.3991/ijim.v16i20.34505
|View full text |Cite
|
Sign up to set email alerts
|

Simple Lightweight Cryptographic Algorithm to Secure Imbedded IoT Devices

Abstract: The internet of things (IoT) revolution has been sparked by the exponential increase in connected devices caused by recent advances in wireless technology. These embedded devices gather, analyze, and send vast data via the network. Data transmission security is a primary problem in IoT networks. Several lightweight encryption/decryption algorithms have been developed for such resource-constraint devices. One of most effective and fast lightweight encryption algorithms for IoT applications is the Tiny Encryptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…It can be implemented in any programming language. The encryption algorithm employs a number called "Delta", which is derived from a golden ratio [13].…”
Section: Tea Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be implemented in any programming language. The encryption algorithm employs a number called "Delta", which is derived from a golden ratio [13].…”
Section: Tea Overviewmentioning
confidence: 99%
“…A mere few lines of source code are sufficient to build TEA. However, TEA does have a limitation when it comes to key scheduling [12,13]. In general, achieving cryptographically secure keys are challenging task in lightweight cryptography due to the limitations of conducted devices [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The art of transforming the original message into incomprehensible codes is to prevent unauthorized parties from POGIL Learning Model-Metaphorming for Mobile-Based Cryptography Creation understanding it [6]. Cryptography involves the analysis and design of mathematical techniques to secure communications from potential threats [5], [45]. Based on several descriptions, it can be concluded that cryptography is the art of creating secret codes using fundamental mathematical principles for security purposes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For this reason, research has been conducted into developing several image encryption techniques. Chaosbased encryption research is one of these subjects [3,4]. There is a close association between chaotic systems and cryptology [5,6].…”
Section: Introductionmentioning
confidence: 99%